Building Brand Creation According to Sharia Concept - Kurnia, Esa (Islamicate Institute, 2024)
This article analyzes brand creation from the perspective of Sharia principles. Conventional branding emphasizes differentiation and emotional connection, but Islamic branding integrates ethical values such as honesty, fairness, and trustworthiness. Using qualitative normative analysis of international and Indonesian literature, Islamic sources, and case studies, the study explores strategies for building Sharia-compliant brands. Findings show that brand creation under Sharia requires embedding Islamic values in identity, communication, and governance, supported by halal certification and regulatory institutions. Theoretically, the research refines branding concepts by incorporating maqasid al-shariah. Practically, it provides Muslim businesses and policymakers with strategies for ethical differentiation, consumer trust, and long-term competitiveness. The article concludes that Sharia branding is both a spiritual obligation and a strategic necessity, with implications for Islamic marketing management and the development of halal industries.